East of the sun - Gregson, Julia (Simon & Schuster, 2009)
Autumn 1928. Three young women are on their way to India, each with a new life in mind. Rose, a beautiful but naïve bride-to-be, is anxious about leaving her family and marrying a man she hardly knows. Victoria, her bridesmaid couldn't be happier to get away from her overbearing mother, and is determined to find herself a husband. And Viva, their inexperienced chaperone, is in search of the India of her childhood, ghosts from the past and freedom. Each of them has their own reason for leaving their homeland but the hopes and secrets they carry can do little to prepare them for what lies ahead in India.